Pengaruh Birth Ball Exercise terhadap Skala Nyeri pada Ibu Bersalin Kala I - Marsilia, Imelda Diana; Herawati, Yulia; Haerunisa, Yuyun (Jurnal Akademika Baiturrahim Jambi, 2025)
A birth ball is a simple physical therapy or exercise that uses a ball, applied to pregnant women, women in labor, and postpartum women. The benefits of using a birth ball are to increase blood flow to the uterus, placenta, and baby, relieve pressure, and provide comfort to the knees and ankles, as well as provide counter-pressure to the perineum and thighs. This position works with gravity to encourage the baby to descend into the pelvic floor, thereby accelerating the labor process. In addition, using a birth ball can help optimize the baby's position during pregnancy and childbirth, balance the body on the ball to help strengthen the back, and help align the baby in preparation for birth. Objective: To determine the effect of birth ball exercise as a method of reducing pain in mothers in stage 1 of labor at the TPMB Y Health Center in West Cikarang District. Research Method: This study used a pre-experimental design with a pre-test-post-test design. The population consisted of 18 people, and the sample size was 18 respondents who met the inclusion criteria, namely physiologically healthy primiparous and multiparous women in labor at TPMB Y, West Cikarang District, from January to February 2024, without a control group. The data collection process involved filling out pretest and posttest observation sheets for respondents and standard operating procedure (SOP) sheets for the provision of birth ball techniques. Results: Based on the Paired T-Test using SPSS, a P-Value of 0.001 (<0.05) was obtained, so it can be concluded that H1 is accepted, meaning that there is an effect of the birth ball technique on the pain scale in mothers in stage I labor at TPMB Y, West Cikarang District. Conclusion: There is an effect of birth ball exercise on the pain scale in women in the first stage of labor at TPMB Y, Cikarang Barat District.